Afghanistan : avoiding another Iraq - Li, Hongyan (2009)
Afghanistan poses a serious challenge to the incoming Obama administration. US military involvement htere has been highly unpopular with the American electorate, yet troop withdrawal from the region is not necessarily the best option in the long run. To help stabilise Afghanistan, the new administration should take into consideration longer term issues.